The Edward Kenway' Social Actions Portrayed in Assassin’s Creed Black Flag - Firmansyah, Muhammad Alvin (English Literature Study Program, 2022)
People's action was usually based on either their rational or irrational motives. One of the examples of rational motive in real life was when a person decided to become a migrant worker overseas to improve the economy of their family, while the irrational motive appeared when one destroyed things due to anger. That kind of action was called social action. In literature, social action is depicted in one character's behavior whether it is related or not related to the goal of the story. The purpose of this study was to find out the depiction of social action performed by the main character and how he achieved his goal based on his social actions in Assassin’s Creed Black Flag novel. The main character of the novel studied was Edward Kenway. This research used one of the theories in sociology of literature proposed by Max Weber, which was called social action. The methodology used was literary criticism. Then, the data were collected by reading the novel and taking notes on the relevant data. The data were then analyzed using social action theory. The results revealed that the form of social actions carried out by Edward Kenway was instrumental action involving ten instrumental rational actions, four value rational actions, eight affectual action, and two traditional actions.